ISLAMIC EDUCATION AND SOCIO-POLITICAL CONDITIONS OF THE BANI ABBASIYAH TIME - Nur Hasanah Hasibuan; Eva Dewi; Amin Maksum (RADJA PUBLIKA, 2024)
Education has a crucial role in human life, providing the ability to understand the universe and maintain existence. In the Islamic context, the importance of education has been recognized since early times, from the time of the Prophet to the time of Khulafaur Rasyidin, the Umayyads, the Abbasids, and up to the present. This research uses the library research method, namely research carried out systematically to collect, manage and conclude data using methods or techniques to find answers to the research discussed. In this research, the information produced comes from drawing conclusions sourced from citing references and abstracted as research findings. The research results show that the Abbasid dynasty has made a very high contribution to Islamic civilization in Islamic history, which is marked by the development of Islamic educational and scientific institutions. This development could not be separated from the socio-political conditions that occurred at that time. The emergence of various Islamic educational institutions during the Abbasid dynasty meant that they had participated in encouraging the progress of the Abbasid dynasty in the field of education. This was an effort that really paid off with satisfaction from what the Muslims did at that time. So, the aim of this research is to find out about Islamic education and the socio-political conditions of the Abbasid era.